Gynura procumbens Prevents Chemoresistance through Inhibition MDR1 Expression on MCF-7 Breast Cancer Cell Line and Sensitizes the Cells to Doxorubicin - Nunuk Aries Nurulita; Edy Meiyanto; Eishou Matsuda; Masashi Kawaichi (Universitas Gadjah Mada, 2012)
The long-term exposure of doxorubicin (Dox) causes enhancement in MDR1 expression that leads tobreast cancer cell resistance. This protein become a serious problem in cancer treatment and also well-knownas negative prognostic factor in breast cancer malignancies. The new approach using natural chemopreventivesubstance was developed to inhibit this resistance progress. This study was aimed to investigate whether ethylacetate fraction of Gynura procumnens (FEG) can prevent chemoresistance through suppressing the MDR1 proteinexpression. MCF-7 cell was used as chemoresistance cell model. The MCF-7 cells were maintained with 100nM Dox-contained medium for five weeks. The chemoprevention effect of FEG was investigated by treatedMCF-7/Dox with sub-toxic concentration of FEG. The cytotoxic properties of MCF-7 cells were determinedusing MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide) assay. Immunofluorescenceand western blotting analysis was performed to detect the MDR1 expression. MCF-7/Dox cells need higherconcentration for inhibiting cell growth, were compared with MCF-7, shown by IC50value. The MDR1 proteinlevel elevated after Dox exposure in time dependent manner. The FEG treatment decreased MDR-1 proteinlevel with dose dependent manner. FEG in combination with DOX potentiates the DOX effect on breast cancercell growth inhibition. The FEG prevents the chemoresistance development in breast cancer cell line, MCF-7induced by Dox through inhibiting MDR1 expression. The additional of FEG enhances Dox effect on cell deathinduction. Thus, FEG could be developed as co-chemotherapy agent for reverse multidrug resistance